THE HISTORY OF THE DEVELOPMENT OF UKRAINIAN NATIONAL SPECIES OF MARTIAL SPORTS - Литвиненко, Андрій (SWorldJournal, 2024)
The article examines the historical origins of modern types of Ukrainian national martial arts. In connection with the formation of the Ukrainian state, the gradual formation of traditional martial culture is analyzed. The emergence and further developmen